Portable mechanical arm / Muhammad Fakrul Haikal Zaflee ...[et al.] - Zaflee, Muhammad Fakrul Haikal; Zahari, Mohamad Farith Izwan; Abdul Rahman Fuad, Ridzuan Fikri; Syed Ali, Syed Saifullah; Azmi, Zainuddin al-Hijri (2015)
The "portamecharm" is a device that will help the user to get unreachable item easily and unsure handling the hazardous material safely. Our product is still in early age of production so our target market is to those were married. It is because our product will help any family members to get any item that in high and narrow place and to ensure user always in safe situation when handling hazardous material. So our target is to sell this product to mothers because usually they will have limited ability to get any item unreachable place. Beside that, they often do the job that involve hazardous material. By using our product, user can make sure the safety and easier them doing something.